Pulmonary Paragonimiasis: A Case Series - Pratima Shah; Rinku Sah; Saugat Pradhan; Priyanka Bhandari; Basundha Khanal; Robin Maskey; Narayan Raj Bhattarai; Ratna Baral (Journal of Nepal Medical Association, 2023)
Paragonimiasis contributes to significant foodborne zoonosis worldwide. The major mode of transmission in humans is by consumption of uncooked or undercooked crabs and crayfish harbouring Paragonimus metacercariae. It begins with symptoms like fever and lower respiratory involvement from a few months to a year, mimicking those of tuberculosis and leading to diagnostic delay. Here, we report two cases of paragonimiasis during a period of nine months. Both cases presented with symptoms of productive cough with rusty sputum, chest pain, along with eosinophilia, and pleural effusion and had a history of consumption of smoked crab from the local river. The diagnosis was established by microscopic demonstration of Paragonimus ova in the sputum. They were treated with praziquantel and recovered. Indeed, it is challenging to diagnose paragonimiasis due to the lack of its specific symptoms but should be considered in the differential diagnosis of eosinophilia and pleural effusion in such lung diseases.